Evaluating farmers' preferences for wastewater: quantity and quality aspects. (6th May 2008) - Birol, Ekin; Koundouri, Phoebe; Kountouris, Yiannis
This paper employs the Contingent Valuation (CV) method to investigate farmers' willingness to adopt a new water resource, namely treated wastewater, and to estimate their Willingness To Pay (WTP) for varying quantities and qualities of treated wastewater for irrigation. A pilot CV study is undertaken with 97 farmers located around Cyprus' Akrotiri aquifer, a common-pool water resource with rapidly deteriorating water quantity and quality. The results reveal that farmers are willing to adopt this new water resource, and they derive the highest economic values from a treated wastewater use programme, which provides high quality treated wastewater, and high water quantity in the aquifer.